A clinical study on linear dermatoses at a teriary care teaching hospital in Davangere - Manangi, Sowmya; Reddy, Marri Anirudh; Sivuni, Aishwarya; Amrutha, Hosalli; Reddy, Suga (International Journal of Research in Dermatology, 2021)
Background: Skin lesions present with innumerable patterns like discoid, petaloid, arcuate, annular, polycyclic, livedo, reticulate, target, stellate, digitate, linear, serpiginous and whorled. Most of the linear lesions follow the Blaschko’s lines. Aim was to study the incidence of linear dermatoses, the age and sex incidence, various types of clinical presentation, various sites of distribution and their clinical correlation. Methods: Detailed history including family history, History of disease documented with clinical examination. After counselling and after recording their consent for the test, skin biopsy along with routine investigations was done wherever needed and the results were evaluated. Results: Lichen striatus was seen in 29.91% followed by linear herpes zoster in 24.7%, linear lichen planus in 18.22%, linear verrucous epidermal nevus in 14.01%, segmental vitiligo in 3.73%, Nevus depigmentosus in 2.33% and others. Maximal cases were asymptomatic and reported for cosmetic reason. Intense itching was the main reason to bring the lichen planus patients and few cases of the lichen striatus patients for treatment. Conclusions: Lichen striatus was found to be more common, female preponderance. Majority of patients showed unilateral distribution more on the extremities. Histopathological correlation shows the importance of histopathology which ultimately changes the management in any given condition.